2021
DOI: 10.1016/j.addbeh.2020.106685
|View full text |Cite
|
Sign up to set email alerts
|

Recollected usage of legal youth gambling products: Comparisons between adult gamblers and non-gamblers in the UK and Australia

Abstract: The UK is rare in allowing a number of gambling forms to be used legally by children under the age of 18. Some previous research indicates that adult problem gamblers are more likely to recollect using these products as children. However, no research has as yet assessed recollected levels of use irrespective of adult gambling status, or investigated these issues in other countries. This is relevant given that at least two of the tested products, coin push machines and crane grab machines, exist in other countr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 26 publications
5
23
0
Order By: Relevance
“…Industry self-regulation can be less effective than government regulation (Mello et al, 2008;Petticrew et al, 2016;Sharma et al, 2010;Xiao et al, 2022), but any potential government action should also consider the robustness of any underlying evidence base. The present results largely supported previous research showing associations between rates of recollected Category D fruit machine usage as a child and adult gambling (Newall et al, 2020b(Newall et al, , 2020a(Newall et al, , 2021, with three out of four associations significant and in the hypothesised direction. Furthermore, rates of subjective confidence were on average high (M = 83.4 out of 100), and zero out of three interaction models were significant, adding further support to these observed associations.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Industry self-regulation can be less effective than government regulation (Mello et al, 2008;Petticrew et al, 2016;Sharma et al, 2010;Xiao et al, 2022), but any potential government action should also consider the robustness of any underlying evidence base. The present results largely supported previous research showing associations between rates of recollected Category D fruit machine usage as a child and adult gambling (Newall et al, 2020b(Newall et al, , 2020a(Newall et al, , 2021, with three out of four associations significant and in the hypothesised direction. Furthermore, rates of subjective confidence were on average high (M = 83.4 out of 100), and zero out of three interaction models were significant, adding further support to these observed associations.…”
Section: Resultssupporting
confidence: 91%
“…Two studies have linked higher rates of recollected usage of Category D fruit machine usage as a child with rates of problem gambling severity among adult gamblers (Newall et al, 2020b(Newall et al, , 2020a. Another study replicated this finding and extended it to also find positive associations between rates of recollected usage of Category D fruit machine usage as a child and the probability of being an adult gambler (Newall et al, 2021). However, these findings could be due to the retrospective nature of the judgments of childhood Category D fruit machine usage.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…Additionally, five games were simulated casino games [13], and a sixth game allowed players to virtually operate physical claw machines (which are an older quasi-gambling product available to children) [14]. These games bore near identical names alluding to gambling at both data collection points, so their primary content likely did not change.…”
mentioning
confidence: 99%
“…Regarding gambling, it was observed that Western countries have become more interested in investigating the problems that derive from this behavior. One explanation of this could be the problems that gambling is causing in their societies, where the problematic gambling sometimes coexists with legal gambling activities, in which the action of betting, for example on sports competitions, is completely normalized ( Newall et al, 2021 , Nikkinen, 2017 , Planzer et al, 2014 , Welte et al, 2017 ). For example, the World Health Organization (WHO) states that studies from countries in Oceania indicate that the potential harms due to gambling are comparable to the harms due to depression and alcohol use disorders ( WHO, 2021a ).…”
Section: Discussionmentioning
confidence: 99%